Delivering Governance in the South Asian Context - Khan, Mussadaq Mohammad (Kuala Lumpur MDC Publishers Printers SDN BHD, 2000)
Delivering governance is a reasoned plea for a rethink of current systems of administration of governments in the South Asian context, with particular reference to the most populous countries viz. Pakistan, India and Bangladesh, which share many common features for historical reasons. Any benefits which may have accrued from the former colonial model today seem overshadowed, due to lack of reforms and structural changes. The author suggest that delivery of "Good" governance requires coherent and relevant delivery systems at all levels of administration, and sets out a scheme to improve the participation by, and representation of, the population at large, through changes in structure and quality of elected representatives at national, provincial/state legislatures and local bodies.
Include Figures.
The concepts and analysis presented could well stimulate interest by other developing countries, to explore their own systems in different light: that of the potential for positive change.
Keywords: Public administration -- South Asia -- Politics and government -- Bureaucracy